Analisis Penerimaan E-learning Madrasah Menggunakan Metode Technology Acceptance Model (TAM) - Hellen Agustina (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Along with the development of digital-based technology and the Covid-19 pandemic which required the school teaching and learning process to be carried out boldly, the Ministry of Religion of the Republic of Indonesia issued a Learning Management System (LMS) product called E-Learning Madrasah which was then applied to madrasah schools. Utilization of E-Learning Madrasah which is then used as digital-based learning (e-learning) at MAN 2 Tulungagung. The use of E-learning Madrasah to assist the teaching and learning process is both challenging and attractive, but in use of its use, there are several obstacles including difficulties for users to understand the features, lack of socialization of use, and ultimately impact on confusion in the operation of E-learning Madrasah. The purpose of this study is to carry out a factor analysis of the use of E-Learning Madrasah at MAN 2 Tulungagung with a quantitative approach, while the measurement model uses the Technology Acceptance Model (TAM) which involves perceived ease of use, perceived usefulness, attitude toward use, behavioral intention to use. The population in this study were students of class XI and XII MAN 2 Tulungagung, totaling 260 students, then processing the data using SmartPLS with the SEM-PLS analysis method. The sampling technique used in this research is probability sampling with proportional stratified random sampling. After conducting thorough data analysis, the research found that the variable's perceived ease of use and perceived usefulness are factors that must be strengthened in their use.